2021
DOI: 10.1039/d0tc05503d
|View full text |Cite
|
Sign up to set email alerts
|

Single-exponential solid-state delayed fluorescence decay in TADF compounds with minimized conformational disorder

Abstract: Construction of rigid TADF compounds allows us to minimize the conformational disorder and obtain single-exponential DF in solid hosts with an exceptional RISC rate of nearly 6 × 106 s−1 and high emission yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…[62,66] Similar results have also been reported in some very recent studies. [6,67] For instance, Hatakeyama and co-workers 6 found that the activation energy barriers are 8.9 and 24 meV, respectively, for the ISC and RISC process of the green TADF emitter of OAB-ABP-1. These above-mentioned results indicate that the real activation energy for RISC from T 1 to S 1 states is not necessarily equal to the ΔE ST values and that even the forward ISC process can be endothermic.…”
Section: Description Of the Intersystem Crossing Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…[62,66] Similar results have also been reported in some very recent studies. [6,67] For instance, Hatakeyama and co-workers 6 found that the activation energy barriers are 8.9 and 24 meV, respectively, for the ISC and RISC process of the green TADF emitter of OAB-ABP-1. These above-mentioned results indicate that the real activation energy for RISC from T 1 to S 1 states is not necessarily equal to the ΔE ST values and that even the forward ISC process can be endothermic.…”
Section: Description Of the Intersystem Crossing Processesmentioning
confidence: 99%
“…[49] Embedded in a rigid matrix (e.g., in doped film states), TADF emitters suffer from inhomogeneous conformer distribution due to the lack of free molecular motions (e.g., rotation), which is evidenced by the multiorder transient PL decays commonly observed in the doped films. [64,67,97] In addition, reorientation and relaxation of the emitting molecules in excited states are restricted in the rigid environment, which of course is related to the rigidity of host materials, leading to the differently stabilized CT states. For TADF emitters, conformers with a higher S 1 level (also a larger ΔE ST ) usually correspond to a higher oscillator strength, which will decay first with a short lifetime, leading to a gradual redshift of prompt fluorescence.…”
Section: Effects Of Host Rigiditymentioning
confidence: 99%
“…6 This conformational disorder, originating from the rotation around the C-N bond has also been investigated in other studies. [7][8][9][10] Furthermore, a molecular design which restricts this torsional motion was reported as an approach to avoid this disorder effect. [11][12][13] However, by using a spiro TADF emitter, the rigidity enforced by the tetrahedral spiro carbon atom gives potential immunity to external conformational distortion of the molecule caused by host interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesized compounds 2PPA, 1PPA, and 1MPA were purified by train sublimation in a Carbolite split tube furnace HZS 12/450. Characterization 1 H NMR and 13 C NMR spectra were recorded on a Bruker Avance III HD (500 MHz), the chemical shifts were referred to chloroform-d3 (7.26 ppm), and the J values are given in Hz. MS spectra were obtained on a Finningan MAT 8500 using electron impact ionization.…”
Section: Purificationmentioning
confidence: 99%
“…Acridine is often used as a donor (D) in emitter molecules because of its rigidity and strong donating feature. [10][11][12][13] Few cases report its use in hosts for red phosphorescence OLEDs. 14,15 Furthermore, what brought our attention to the acridine group is that it has a higher triplet energy than carbazole (due to less conjugation).…”
Section: Introductionmentioning
confidence: 99%